Making parasocial identification tangible: Can film memorabilia strengthen travel intention? - Ariel Zoltán Mitev; Anna Rita Irimiás; Gábor Michalkó (Journal of Tourism, Heritage & Services Marketing)
Purpose: The main purpose of this paper is to expand on the theories of parasocial identification and transitional objects, and to pioneer the investigation into how imaginative practices become tangible aspects of tourist behavior.